2019
DOI: 10.1111/jace.16276
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and property relationships in the double diboride ceramic composites by spark plasma sintering of TiB2 and NbB2

Abstract: Bulk titanium diboride-niobium diboride ceramic composites were consolidated by spark plasma sintering (SPS) at 1950°C. SPS resulted in dense specimens with a density exceeding 98% of the theoretical density and a multimodal grain size ranging from 1 to 10 μm. During the SPS consolidation, the pressure was applied and released at 1950 and 1250°C, respectively. This allowed obtaining a twophase composite consisting of TiB 2 and NbB 2 . For these ceramics composites, we evaluated the flexural strength and fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…A similar fracture surface has been observed for the TiB 2 /NbB 2 double diboride composite, as the formation of a fine sub-grain fracture or the formation of the needle-like fracture for the NbB 2 . 6 Some of these needle-shaped grains appeared at 1200 • C in Ref. [6], coinciding with the strength increase.…”
Section: Evaluation Of Flexural Strength and Fracture Peculiaritiesmentioning
confidence: 86%
See 2 more Smart Citations
“…A similar fracture surface has been observed for the TiB 2 /NbB 2 double diboride composite, as the formation of a fine sub-grain fracture or the formation of the needle-like fracture for the NbB 2 . 6 Some of these needle-shaped grains appeared at 1200 • C in Ref. [6], coinciding with the strength increase.…”
Section: Evaluation Of Flexural Strength and Fracture Peculiaritiesmentioning
confidence: 86%
“…This observation suggests that there is a phase in the composite that not only contributes to the macroscopic plastic deformation but also limits the crack propagation by, presumably, a microplastic field in the front of the crack propagation. 6,62,63 With an increase in the loading rate up to 2.5 mm/min, it was possible to achieve the fracture of the specimen. The fracture analysis suggests that the majority of the phases still predominantly underwent an intergranular fracture, which is not typical for bulk diborides at these temperatures, 5 and may explain the relatively high strength at elevated temperatures.…”
Section: Evaluation Of Flexural Strength and Fracture Peculiaritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prepregged fabric was next cut No references were found on modeling for CMCs, though experimental studies o ing process have been reported. Studies o derived SiC ceramic 25 and SiC/SiC c shown that porosity decreases and mecha prove with the increasing number of PIP show that increasing pyrolysis temperatu tration of SiC fillers in polycarbosilane improved mechanical properties in two-d SiC (C/SiC) composites fabricated using Starting with pyrolysis of a "cured prepreg-based composite, each processin process involves infiltration of a precera porous preform followed by a py which the polymer is converted into ceram cess modeling is focused on these two ste Modeling of infiltration of liquids in well-studied subject, especially in the where it is used to model seepage of wa soils and rocks. 29,30 The physics of resin under pressure is similar to the seepage pr lar approaches have been used also to mod into a mold containing fiber mats.…”
Section: Methodsmentioning
confidence: 99%
“…No references were found on modeling of the PIP process for CMCs, though experimental studies on this manufacturing process have been reported. Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
Section: Introductionmentioning
confidence: 99%